2012
DOI: 10.1063/1.4765334
|View full text |Cite
|
Sign up to set email alerts
|

A new, definitive analysis of a very old spectrum: The highly perturbed A2Πu–X 2Πg band system of the chlorine cation (${\rm Cl}_2^ +$ Cl 2+)

Abstract: The laser-induced fluorescence spectrum of jet-cooled chlorine cation has been recorded in the 500-312 nm region with high sensitivity and rigorous vibrational and spin-orbit cooling. More than 80 bands of the highly vibrationally perturbed A (2)Π(u)-X (2)Π(g) electronic transition have been detected and shown to originate from the Ω = 3/2 spin-orbit component of v = 0 of the ground state. The spectrum extends some 3700 cm(-1) to the red of any previously published report and the 0-0 band has been identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 30 publications
3
21
1
Order By: Relevance
“…However, it is only very recently that a full understanding of the A + 2 u, 3/2 → X + 2 g, 3/2 band system, including a complete treatment of the interaction between the A + 2 u, 3/2 and the B + 2 u, 3/2 states, could be reached, based on a new high-resolution measurement of the laser-inducedfluorescence spectrum of Cl + 2 and ab initio calculations. 3 The low temperature of the Cl + 2 sample used in this study, however, prevented the observation of transitions involving the A + 2 u, 1/2 state, the assignment of which remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is only very recently that a full understanding of the A + 2 u, 3/2 → X + 2 g, 3/2 band system, including a complete treatment of the interaction between the A + 2 u, 3/2 and the B + 2 u, 3/2 states, could be reached, based on a new high-resolution measurement of the laser-inducedfluorescence spectrum of Cl + 2 and ab initio calculations. 3 The low temperature of the Cl + 2 sample used in this study, however, prevented the observation of transitions involving the A + 2 u, 1/2 state, the assignment of which remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…8, 17, and 18). These studies indicated that a broad range of vibrational levels of the X + and A + states could be studied (σ g ) 2 (π u ) 4 (π * g ) 3 X + 2 g (σ g ) 2 (π u ) 3 (π * g ) 4 A + 2 u (σ g ) 1 (π u ) 4 (π * g ) 4 2 + g (σ g ) 2 (π u ) 4 (π * g ) 2 (σ * u ) 1 4 − u , 2 u , 2 − u , 2 + u at high resolution by pulsed-field-ionization zero-kineticenergy (PFI-ZEKE) photoelectron spectroscopy and that information on the mechanisms leading to ion-pair formation in the photoionization of Cl 2 might be obtained from such studies. PFI-ZEKE photoelectron spectra of the low vibrational levels (v + ≤ 6) of the X + state with partial rotational resolution were reported by Li et al 9 who also determined precise values of the first adiabatic ionization energy of Cl 2 and of the threshold for Cl + ( 1 D 2 ) + Cl − ( 1 S 0 ) ion-pair formation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations